Enhancing Customer Relationship Management in Retail: A Case Study of Reliance Trends - Grancy Kaneria; Divya Shah; Jaykishan Gautam; Jignesh Vidani (International Journal of Educational and Life Sciences, 2024)
Within the dynamic realm of retail, the implementation of Customer Relationship Management (CRM) is essential for cultivating customer satisfaction, fostering loyalty, and ultimately propelling sales growth. This case study explores the CRM strategies utilised by Reliance Trends, a prominent fashion retail brand in India, to examine how it effectively utilises CRM practices to stay ahead in the competitive market. Using a qualitative case study approach, this research delves into the effectiveness of Reliance Trends' CRM initiatives in boosting customer satisfaction and loyalty. It also aims to identify any areas that could be enhanced. This study underscores the importance of CRM in retail environments, emphasising its influence on tailored customer interactions and the customisation of global strategies to fit local markets. Our findings provide valuable insights into CRM practices, highlighting both their strengths and weaknesses. Additionally, we offer recommendations for enhancing the effectiveness of CRM strategies.